2001
DOI: 10.1103/physrevlett.87.067005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Tunneling Spectra inBi2Sr2CaCu2

Abstract: New break-junction tunneling data are reported in Bi(2)Sr(2)CaCu(2)O(8+delta) over a wide range of hole concentration from underdoped (T(c) = 74 K) to optimal doped (T(c) = 95 K) to overdoped (T(c) = 48 K). The conductances exhibit sharp dips at a voltage, Omega/e, measured with respect to the superconducting gap. Clear trends are found such that the dip strength is maximum at optimal doping and that Omega scales as 4.9kT(c) over the entire doping range. These features link the dip to the resonance spin excita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
174
3
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(222 citation statements)
references
References 24 publications
41
174
3
4
Order By: Relevance
“…Such an effect was observed recently in optimally doped Bi 2 Sr 2 CaCu 2 O 8−δ break junctions. 37 We also observe negative behavior at higher bias in the coherent tunneling limit, but note that in reality, the tunneling matrix element will have both coherent and incoherent contributions (especially at higher voltages), and thus will be a weighted average of the dashed and full curves in Fig. 20.…”
Section: E Tunneling Spectramentioning
confidence: 69%
See 2 more Smart Citations
“…Such an effect was observed recently in optimally doped Bi 2 Sr 2 CaCu 2 O 8−δ break junctions. 37 We also observe negative behavior at higher bias in the coherent tunneling limit, but note that in reality, the tunneling matrix element will have both coherent and incoherent contributions (especially at higher voltages), and thus will be a weighted average of the dashed and full curves in Fig. 20.…”
Section: E Tunneling Spectramentioning
confidence: 69%
“…8 The dip feature has been observed in tunneling spectra of the single Cu-O 2 layer compound Tl 2 Ba 2 CuO 6 as well. 36 In order to extract information about the bosonic mode which would produce a dip feature in the tunneling conductance, a systematic study as a function of doping was performed in break junction tunneling spectroscopy by Zasadzinski et al 37 There, the doping dependence in Bi 2 Sr 2 CaCu 2 O 8−δ of the peak-dip-hump structure was determined over a wide range of doping. It was found that the dip-peak energy separation, Ω, follows T c as Ω = 4.9k B T c .…”
Section: B C-axis Tunneling Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction affects the one-electron spectra and is observable in the single-electron spectroscopies. Although the strength of this interaction has been a matter of controversy, 31,32 there is evidence that peculiar signatures observed in photoemission, [33][34][35][36] tunneling, [37][38][39][40][41] and optical conductivity 42,43 result from this interaction. Yet, a firm consensus has not been reached: Optical phonons often exist in the cuprates at similar energies, and distinguishing the effects of the two kinds of excitations has proven difficult.…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective solutions to minimize these effects is to decrease the coupling between CuO 2 layers by intercalation of Bi2212 with an inert molecule such as HgBr 2 , I 2 , HgI 2 . IJJ tunneling spectroscopy studies of HgBr 2 intercalated crystals can reveal crucial features [9] obtained from conventional tunnel junctions such as dip and hump which are linked to mechanism of superconductivity [10]. Recent advances in IJJ research have focused on utilizing superconductors in spintronics (spin-based electronics) and heterostructure junctions have been fabricated for spin-dependent transport experiments.…”
mentioning
confidence: 99%